1980
DOI: 10.1017/s0079497x00009385
|View full text |Cite
|
Sign up to set email alerts
|

Two Late Bronze Age Settlements on the Kennet Gravels: Excavations at Aldermaston Wharf and Knight's Farm, Burghfield, Berkshire

Abstract: One of the major problems of British prehistory has been the contrast between the mass of Late Bronze Age metalwork and the rarity of contemporary settlements. The Berkshire river gravels are one area in which a high proportion of bronze objects is recorded in apparent isolation. With the increasing recognition of Late Bronze Age pottery, however, it has been possible to identify domestic finds of this period among the artefacts from gravel pits around Reading. Part of the gap in the settlement record has also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Within the dynamic and ever-changing households of Middle Bronze Age southern England, there were many worlds of possibility, not just one. (Brown 1988), and Aldermaston Wharf, Berkshire (Bradley et al 1980). This suggests considerable variability in the construction of place and perhaps also in patterns of land tenure during the Late Bronze Age.…”
Section: Future Workmentioning
confidence: 99%
“…Within the dynamic and ever-changing households of Middle Bronze Age southern England, there were many worlds of possibility, not just one. (Brown 1988), and Aldermaston Wharf, Berkshire (Bradley et al 1980). This suggests considerable variability in the construction of place and perhaps also in patterns of land tenure during the Late Bronze Age.…”
Section: Future Workmentioning
confidence: 99%
“…One fieldwork report considers the potential for a site's inhabitants to produce economic surplus, and thus to gain access to exchange networks involving prestige items (Bradley et al 1980). One fieldwork report considers the potential for a site's inhabitants to produce economic surplus, and thus to gain access to exchange networks involving prestige items (Bradley et al 1980).…”
Section: Interpretative Themesmentioning
confidence: 99%
“…As today, local drainage conditions clearly affected subsistence strategies. Bradley et al (1980), in a study of the Kennet valley around Reading, showed that sites with access to freely draining soils produced much greater quantities of cereals than those on poorly drained soils or land prone to flooding. Moreover, while loomweights came from all sites, the latter group lacked spindle whorls, which may be indicative of seasonal occupation in the damper areas.…”
Section: Eba Guttmann and J Last Late Bronze Age Landscapes S Hormentioning
confidence: 99%
“…While many fit the double ring pattern advanced by Guilbert (1981;, the axial symmetry perceived by him at numerous sites is not matched here, even in Structure 1. On the other hand, many other earlier 1st millennium BC buildings are similarly irregular, including those within the ringwork at Mucking North, and at Thames valley sites like Aldermaston Wharf (Bradley et al 1980), Petters Sports Field (cf O'Connell 1986Needham 1993 for the difficulty of interpreting post-holes), and Stanwell, where structures could only be tentatively identified.…”
Section: Round-houses and Fenced Enclosuresmentioning
confidence: 99%